Sovereign wealth funds and foreign policy: How Saudi Arabia, the UAE and Qatar invest in their power - Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2026)
Five of the world's most active and largest sovereign wealth funds are to be found in the Gulf Region: the Saudi Public Investment Fund (PIF), the Qatar Investment Authority (QIA) and the United Arab Emirates' Abu Dhabi Investment Authority (ADIA), Mubadala and ADQ. These funds not only serve to convert oil revenues into investment capital, thereby enabling the transition from rent-based to more diversified economies; they also contribute to expanding the foreign policy capabilities of the countries in which they are based. Institutional and personnel linkages enable the Saudi, Qatari and UAE governments to deploy their funds strategically, which, in turn, allows them to significantly expand their hard, soft, and sharp power - for example, through domestic and foreign investments in sectors such as armaments, media, sports and new technologies as well as through cooperation with politically influential actors. At the same time, the Gulf monarchies seek to portray their sovereign wealth funds as apolitical and purely profit-oriented - a narrative that is facilitated by the establishment of subsidiaries or cooperation with private equity firms. Understandably, Germany and its European partners have an interest in attracting sovereign wealth funds as investors, but they must not overlook the risks involved. These include third parties gaining access to critical infrastructure, sensitive military and security technology being leaked and the Gulf monarchies exercising political influence. Further, Germany and the EU must take a more fundamental look at how the three Gulf monarchies have increased their foreign policy options through the sovereign wealth funds. This is important as the actions of Saudi Arabia, the UAE and Qatar - at both the regional and international level - are at times contrary to German and European interests.
Keywords: 320